Constructing consistent energy scenarios using cross impact matrices - Roland Broll; Gerald Blumberg; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance (HEMF), 2020)
The ongoing transformation process towards a low or even zero emission energy system is facing a steadily increasing complexity, notably through variable renewable energies and sector coupling. At the same time, the necessity for long-term decisions associated with high capital costs remains. Hence methods are desirable that help decision makers to manage the broad range of possible futures without overly simplifying the interplay of multiple developments in many societal, technological, and economic fields. This requires the inclusion of expert knowledge from different domains without put-ting an excessive workload on these experts. The paper at hand proposes an efficient two-stage approach to derive a limited set of scenarios. In the first step, the focus is on establishing the key causal relationships and derive the key exogenous drivers for future developments. In the second step, their interdependency is then assessed in more detail and consistent scenarios are derived. The approach builds on two existing methods, the "ADVanced Impact ANalysis (ADVIAN)" and the "Cross-impact balances analysis" (CIB), yet these are refined and tailored both in terms of improved computation approaches and advanced assessment indicators. The newly developed approach is applied to the case of network extension planning as this is charac-terized by both significant complexity increases and long-term investment decisions under high uncer-tainty. Starting with many potential driving factors, just a few key exogenous drivers are identified and four consistent scenarios up to the year 2050 are derived with a limited amount of expert assessment workload. The methodology enables thus the development of consistent socio-techno-economic scenarios that may also serve as framework for more detailed model-based assessments of energy-system develop-ments.
Keywords: 330; energy scenarios; cross impact matrix; indirect and direct impacts; exogenous drivers and endogenous factors; cross impact balances; scenario-reduction; consistent scenarios; consistency analysis; network expansion scenarios